Distributed fault correlation scheme using a semantic publish/subscribe system - KEENEY, JOHN; O'SULLIVAN, DECLAN (IEEE, 2008)
Increasingly there is a demand for more scalable fault management schemes to cope with the ever increasing growth and complexity of modern networks. Current distributed fault correlation schemes typically adopt rigid topologies, which require great effort in topology configuration. In this paper, we introduce a distributed fault correlation scheme which addresses this problem by using semantic-based publish/subscribe middleware. This provides loose coupling, robustness and scalability properties for the scheme.
PUBLISHED
Keywords: Computer Science